2000
DOI: 10.1177/159101990000600402
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Traumatic Carotid-Cavernous Fistula

Abstract: From 1986 to the end of 1998, 482 cases of traumatic carotid-cavernous fistula (TCCF) were treated by means of intravascular embolisation technique. The experience is overviewed in this article. Many kinds of detachable balloon catheters (including Chinese made detachable balloon catheters), coils and cyanoacrylate were used as embolic materials. Transcervical, transfemoral, anterior communicating artery, posterior communicating artery approach, or transvenous approach were selected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Over the years, worldwide studies have showed varying degrees of success at achieving the ideal outcome. Internal carotid artery preservation rate in reviewed studies ranged between 40% and 84% 13,14 and CCF occlusion between 86% and 100%. 13,15 To date, scant local data exist to our knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Over the years, worldwide studies have showed varying degrees of success at achieving the ideal outcome. Internal carotid artery preservation rate in reviewed studies ranged between 40% and 84% 13,14 and CCF occlusion between 86% and 100%. 13,15 To date, scant local data exist to our knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…The two common treatment options for TCVI are surgery and endovascular coil embolization. Endovascular intervention is feasible in cases of AVF, 9,25,30 and treatments of pseudoaneurysm have been discussed elsewhere. 14,25,29 Based on expert opinion, the type of TCVI and anatomical considerations, such as size, location, and morphological features, determine which treatment is most appropriate for the individual patient.…”
Section: Discussionmentioning
confidence: 99%
“…Recurrence after ICA occlusion/PAO has been seen due to reverse filling of thefistula through the distal ICA. 5 Studies have shown recurrence Recurrence of CCF after Treatment Kumar et al…”
Section: Discussionmentioning
confidence: 99%
“…1,3 However, there are only very few instances of recurrence of CCF following endovascular PAO. 4,5 We present two cases of CCF with recurrence following complete exclusion by PAO. The factors predisposing to this unusual occurrence are discussed.…”
Section: Introductionmentioning
confidence: 99%